On the good life of disgust. L’ésthetique du stercoraire and the postmodern society (Lebenswelt. Aesthetics and philosophy of experience., 2013)
Starting from a debate which took place at the beginning of the twenty-first century between Jean Clair and Arthur C. Danto, we will focus on the link between art and disgust, because we wish to show what art is now ‘doing’ with disgust. Our hypothesis is that art is part of the general process of self-reshaping that is underway in today’s capitalist societies. Therefore, by commenting Aurel Kolnai’s phenomenological analysis of disgust, we will gain the tools to try to show how disgust could be a crucial factor in the above process. Finally, we will recall the work of artists such as Pasolini, Nebreda, and McCarthy, in order to suggest how art could use disgust and have an actual political effect by orienting that process. All this is possible, because disgust has to do with the good life.